Using the ELECTRE Tri Method to Categorize Roads: The Case of the Ngaoundéré Town in Cameroun - Guidana, Gazawa Frédéric; Kali, Abdelaziz; Tanone, Demas (European Journal of Applied Sciences, 2024)
A road network is the set of roads that enable people and goods to move from one point to another. It provides access to important infrastructures such as health and education services. In Cameroon, the road network inherited from the colonial era poses major challenges. The case of Ngaoundéré, capital of the Adamaoua region, a transit city between the regions of the far south of Cameroon and the far north, sees its road networks frequently used. Given the increase in traffic, poor user behavior and deterioration, the problem of road safety (assaults, frequent accidents) and the deterioration of the means of locomotion, which contributes most to greenhouse gas emissions (GHG), has arisen. This work involves assigning the various roads to distinct categories in order to highlight potentially dangerous roads requiring special attention. To do this, we’ll be building a more or less exhaustive, coherent and non-redundant set of criteria enabling a multi-criteria evaluation of these different roads. Seven relevant and coherent criteria (distance, type, condition, season, infrastructure, behavior and aggression) were selected. We used the ELECTRE Tri method, derived from the AMCD assignment problem, to categorize these roads. After a robustness analysis, this method enabled us to identify at-risk roads in the city of Ngaoundéré from among 42 essential ones. Some 95.24% of Ngaoundéré’s roads are poor and 4.76% are hazardous. According to these criteria, the city does not have any roads in the Good or Very Good categories.